Pasteurella multocida vertebral osteomyelitis, myositis and epidural abscess in a diabetic cirrhotic patient. (2019) - Malek, Alexandre E.; Fares, Johny E.; Raad, Issam I.; Ericsson, Charles
Abstract: Pasteurella multocida is frequently associated with soft tissue infections related to animal bites or scratches. These infections are usually mild but can lead to serious complications especially in high-risk patients. We present a chronic Pasteurella. multocida vertebral osteomyelitis with extensive spondylodiscitis, myositis and epidural abscess in a patient with diabetes and liver cirrhosis. Pasteurella multocida should be suspected in bone and soft tissue infections even if the site of infection is distant to the site of the animal bite, scratch or lick, especially in high-risk patients.